(untitled) (Journal of Bangladesh Institute of Planners, 2011)
Study on trip generation is one of the four steps of conventional transportation modelling process. Trip generation of an urban area is related with its socio-economic and land use characteristics. Applying this model in the study area of Savar pourashava, attempt has been made to find out the factors, which are related with trip generation. Based on some selected variables or factors used in the spatial regression analysis, the study tries to estimate the total number of trips generated from each ward of the pourashava. Moreover, the impact of trip generation on road transport system is identified in the study to recommend on minimizing its negative impacts for smooth operation of traffic and as well as for proper traffic management. Journal of Bangladesh Institute of Planners Vol. 4. Dec 2011, pp. 33 - 43